IMPLEMENTASI STANDAR AKUNTANSI KEUANGAN ENTITAS PRIVAT DALAM PENYUSUNAN LAPORAN KEUANGAN PADA TOKO SEMBAKO AMANAH SUKSES KECAMATAN TAMBAKSARI - Annisa Rahma Qur’aini; Cholis Hidayati (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2026)
This study aims to analyze the implementation of Private Entity Financial Accounting Standards (SAK EP) in the preparation of financial reports at the Amanah Sukses Grocery Store located in Tambaksari District, Surabaya, and to identify obstacles in its implementation. This research uses a qualitative approach with a case study research type. Data collection techniques are carried out through observation, in-depth interviews, and documentation. The main informants in this study are the owner and manager of the store. The results of the study indicate that financial recording at the Amanah Sukses Grocery Store is still carried out simply and manually, which is limited to recording cash inflows and outflows, the preparation of financial reports is not fully in accordance with the provisions of SAK EP, because it does not include a report on financial position, profit and loss report, a report on changes in equity, a systematic cash flow report, and notes to the financial statements. The main obstacles in the implementation of SAK EP include the owner's limited understanding of accounting standards, limited human resources, and the suboptimal use of technology in financial recording. This study recommends the need for accounting assistance and training for MSMEs, as well as the use of a simple digital recording system so that the implementation of SAK EP can be carried out gradually and sustainably.